A review of the Mexican species of Alloeorhynchus Fieber (Hemiptera: Heteroptera: Nabidae: Prostemmatinae) with description of six new species, new distributional records, and key to the species - Brailovsky, Harry; Barrera, Ernesto (Zootaxa, 2017)
The genus Alloeorhynchus Fieber (Nabidae) from Mexico is revised. Three species A. moritzii, A. nigrofasciatus and A. nigrolobus are recorded for the first time from Mexico. Six new species are described: A. aureus (from Chiapas and Veracuz), A. bellatulus (from Chiapas and Oaxaca), A. convolutus (from Oaxaca and Veracruz), A. epigaeus (from Guerrero, Michoacan and Oaxaca), A. macer (from Colima, Jalisco and Sonora), and A. vergrandis (from Chiapas and Veracruz). New distributional records for A. trimacula (Stein), the only previously known Mexican species, are added. A key to the species recorded from Mexico is included. Notes on the biology of some species are given. Pictures of the dorsal habitus and parameres are provided.